Association Between Self-Efficacy And Burnout Among Medical Students : A Systematic Review - Reza Aries; Arif Rachman; Agus Sutarman; Arfiyanti (Journal of Innovation Research and Knowledge, 2026)
Burnout is a common psychological problem among medical students due to high academic demands, intensive workloads, and continuous pressure to achieve professional competence. One factor that may help reduce the risk of burnout is self-efficacy, defined as an individual's belief in their ability to successfully perform tasks and overcome challenges. This study aimed to identify and synthesize the available evidence regarding the association between self-efficacy and burnout among medical students. A Systematic Literature Review (SLR) was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines Literature searches were performed in PubMed, Scopus, and Google Scholar using the keywords “self-efficacy,” “burnout,” and “medical students.” Articles published between 2016 and 2025, available in full text, and meeting the inclusion criteria were selected for analysis. After the screening process, five studies were included in the qualitative synthesis. The findings consistently demonstrated a significant association between self-efficacy and burnout among medical students. Most studies reported a negative relationship, indicating that students with higher levels of self-efficacy tended to experience lower levels of burnout. These findings suggest that self-efficacy serves as an important protective factor that enables medical students to cope more effectively with academic stress and reduce the likelihood of burnout. In conclusion, self-efficacy is negatively associated with burnout among medical students. Strengthening self-efficacy may be an effective strategy to reduce burnout and promote psychological well-being throughout medical education.